Reproductive cycle of cultured chub mackerel (Scomber japonicus), in a land-based tank system in Jeju Island, Korea - Baek, Seong Il; Ji, Seung Cheol; Cho, Jeong-Hyeon (Frontiers in Marine Science, 2025)
IntroductionChub mackerel (Scomber japonicus) is an economically important fishery resource in Northeast Asia. However, increasing consumer demand combined with declining wild stocks has highlighted the urgent need to develop aquaculture techniques for stable production. Currently, large-scale larval production is hindered by insufficient knowledge of broodstock reproductive biology under aquaculture conditions. Thus, identifying reproductive patterns of chub mackerel in land-based systems is essential to optimize breeding strategies and juvenile production. Methods: We monitored the reproductive characteristics of approximately one-year-old chub mackerel broodstock (initial weight 250 g), maintained in a land-based tank under natural temperature and photoperiod conditions for 12 months. Monthly sampling included measuring gonadosomatic indices (GSI), histological analysis of gonadal developmental stages, plasma sex steroid hormones (testosterone [T], 11-ketotestosterone [11-KT], 17β-estradiol [E2]), and expression analysis of reproduction-related genes (fshβ and lhβ).Results and DiscussionMale GSI markedly increased from March to June, peaking between April and June. Female GSI rose from March, reaching its peak in June. Histologically, gonads of both sexes showed four distinct developmental stages. Males entered late spermatogenesis in March, spermiation in April, and post-spawning by July. Females progressed through early vitellogenesis in March, late vitellogenesis by May, and post-spawning by July. Actual spawning events, confirmed by the presence of post-ovulatory follicles and egg release, occurred from late May to mid-July. This reproductive season, initiated by rising seawater temperatures, coincides with the natural spawning period reported for wild populations, suggesting that aquaculture conditions effectively replicated environmental spawning triggers. Plasma steroid hormones (T, 11-KT, and E2) peaked during key reproductive phases, closely mirroring gonadal development. Concurrently, expression of reproductive genes (fshβ, lhβ) correlated significantly with plasma hormone fluctuations, indicating regulatory roles of follicle-stimulating hormone and luteinizing hormone in gonadal maturation and spawning. These findings enhance our understanding of reproductive physiology in chub mackerel under controlled conditions, providing critical data for optimizing broodstock management and establishing reliable spawning strategies essential for sustainable aquaculture production.